Model of Drug Abuse Prevention in Swampland - Abdul Rahman; Amin Rejo; Dadang Hikmah Purnama; Mada Apriandi Zuhir (Dinasti International Journal of Education Management And Social Science, 2024)
In Indonesia, swamplands are spread across several regions, one of which is Palembang City, which has the highest level of drug abuse cases among districts/cities in South Sumatra Province. In order to tackle this problem, a special approach is needed that takes into account the geographical and socio-economic conditions in swamplands. This study aims to analyze drug abuse prevention programs in Palembang City and develop an effective drug abuse prevention model in particular swamplands. This research used qualitative methods with triangulation techniques to gain an in-depth and comprehensive understanding of the drug abuse program in Palembang City's swamplands. Informants in this study included three groups: drug abusers, stakeholders, and the community. A drug abuse prevention model in swampland must take into account the unique conditions of the area, such as limited accessibility and possibly low levels of community welfare. Effective approaches include improving access to education and health services, economic empowerment through local programs, and active community involvement in prevention efforts. In addition, these strategies need to be tailored to the demographic and socioeconomic characteristics of the local population to ensure the success and sustainability of prevention programs.